Randomized controlled trial (RCT) study on climate digital advisory tools, credit and insurance in Ghana - Arouna, A.; Aboudou, R.; Gbede, T.R.; Yergo, W.G. (Africa Rice Center, 2024)
This report presents a baseline survey of a randomized controlled trial (RCT) focusing on the efficacy of digital climate advisory tools, credit, and insurance among smallholder farmers in Ghana. In response to climate change challenges, these interventions aim to bolster agricultural resilience and mitigate risks. This study, conducted under the Excellence in Agronomy (EiA) initiative, aims to enhance agricultural productivity, income stability, and climate resilience among smallholder farmers. The baseline survey included demographic information, farming practices, and current access to digital tools, credit, and insurance. By establishing a baseline, this study sets a stage for assessing the changes in productivity, income stability, and resilience over time. This study employs a mixed-methods approach that combines quantitative and qualitative data to establish a comprehensive understanding of the current context. Data quality assurance procedures including enumerator training and data validatio